2022
DOI: 10.1371/journal.ppat.1010321
|View full text |Cite|
|
Sign up to set email alerts
|

An in vitro method for inducing titan cells reveals novel features of yeast-to-titan switching in the human fungal pathogen Cryptococcus gattii

Abstract: Cryptococcosis is a potentially lethal fungal infection of humans caused by organisms within the Cryptococcus neoformans/gattii species complex. Whilst C. neoformans is a relatively common pathogen of immunocompromised individuals, C. gattii is capable of acting as a primary pathogen of immunocompetent individuals. Within the host, both species undergo morphogenesis to form titan cells: exceptionally large cells that are critical for disease establishment. To date, the induction, defining attributes, and under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Capsule size correlates with virulence, although not case-fatalit [ 61 ]. Notably, C. gattii seems to have a greater propensity to form titan cells [ 62 ]. Titan cells are abnormally sized (>10 µm) yeast cells that have an immunomodulatory role and potential roles in the pathogenesis of cryptococcosis [ 63 ].…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
“…Capsule size correlates with virulence, although not case-fatalit [ 61 ]. Notably, C. gattii seems to have a greater propensity to form titan cells [ 62 ]. Titan cells are abnormally sized (>10 µm) yeast cells that have an immunomodulatory role and potential roles in the pathogenesis of cryptococcosis [ 63 ].…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
“…It has been shown that this ability to undergo such specific morphological transformation is unique for pathogenic yeasts of the Cryptococcus species complex [30]. It was confirmed then by two independent research centers that, as in the case of members of the C. neoformans species complex, species of the complex C. gattii, were able to form Titan cells, respectively according to commonly known in vitro serum protocol [31] and the newest protocol based on RPMI medium [114]. Moreover, recently it has been shown that strategies for titanization in case of members of C. gattii and C. neoformans species complexes are significantly different.…”
Section: Titan Cells Formation Is Unique For Members Of the Cryptococ...mentioning
confidence: 90%
“…While for C. neoformans typical is synchronous occurrence of cells enlargement and polyploidization, in the case of C. gattii we can observe delay in DNA endoreduplication and cell growth to around 30 μm as a haploid cell. Only after ~ 3 days incubation under titanization conditions DNA endoreduplication can be observed, which finally leads to uninucleate polyploid cells [114]. Moreover, this process was equally effective.…”
Section: Titan Cells Formation Is Unique For Members Of the Cryptococ...mentioning
confidence: 99%
See 1 more Smart Citation
“…neoformans [ 92 96 ]. We and others have recently investigated titan cell formation across the broader Cryptococcus species complex, which has revealed some subtle differences between lineages [ 44 ]. The impact of these differences on the CGSC–host interaction remains largely unknown [ 97 99 ].…”
Section: Understudied Virulence-associated Phenotypes Of C ...mentioning
confidence: 99%